Interdisciplinaridade e Universidade - João Paulo Avelãs Nunes (III Conferências e Debates Interdisciplinares, 2016)
The theoretical wealth and the polysemy of the concept interdisciplinarity, whose boundaries occur frequently not very well defined in relation to related concepts such as multidisciplinary and transdisciplinary, have contributed for sometimes not being very clear the methodological contours of interdisciplinarity,. But there is a growing conviction among academics and researchers about the need to break with the epistemological and methodological limitations of the traditional disciplinary framework. The coexistence of multiple views on the same issue, essential for the understanding of reality in its complexity, has been gaining more and more space between researchers and teachers. But this unanimity on the benefits and potential of interdisciplinarity to the advancement of knowledge, both in research and in teaching, has taken sometime to find satisfactory reception in the definition of methodologies and interdisciplinary research practices at the University. The attempt to find answers to this apparent discrepancy was at the center of the authors concerns and their contributions gathered in this book.